Psychological working conditions and predictors of occupational stress among nurses, Salaga Government Hospital, Ghana, 2016 - Kaburi, B.B.; Bio, F.Y.; Kubio, C.; Ameme, D.K.; Kenu, E.; Sackey, S.O.; Afari, E.A. (Pan African Medical Journal (PAMJ), 2019)
Introduction: occupational stress is a recognized health problem among nurses. Globally, its prevalence varies between 9.2% and 68.0%. It detracts from nurses' quality of life and efficiency of job performance. In Ghana, we do not know the important contributory factors to this problem. Our study sought to identify the important predictors of occupational stress among nurses. Methods: in January 2016, we conducted an institutionalbased survey among nurses of Salaga Government Hospital. They completed a five-point Likert type questionnaire adopted from the British Psychological Working Conditions Survey, and the Nurse Stress Index. Across 30 predictor variables, a mean score of 4.00 to 5.00 represented high to extreme occupational stress. We performed bivariate and multivariate analyses to identify important predictors of occupational stress at 95% confidence level. Results: of 167 nurses, 58.1% (97) were females. Respondents who experienced high to extreme stress levels had a 2.3 times odds of reporting sickness absence (CI: 1.03-5.14). Sources of occupational stress included: manual lifting of patients and pieces of equipment (OR: 16.23; CI: 6.28 - 41.92), the risks of acquiring infections (OR: 14.67; CI 5.90 - 36.46), receiving feedback only upon unsatisfactory performance (OR: 28.00; CI: 9.72 - 80.64), and inadequate opportunities for continuous professional development (OR: 63.50; CI: 19.99 - 201.75). Conclusion: the working conditions of nurses were stressful. The most significant predictors of occupational stress were poor supportive supervision by superiors, lack of adequate skills to perform routine tasks, uncertainty about their job role, and the lack of adequate opportunities for career advancements.
Research Article
Keywords: Nurses; occupational stress; predictors; psychological working conditions Salaga Government Hospital; Ghana